Sortilin/Omentin-1 ratio in peripheral artery disease: A cross-sectional study on 295 unselected elderly patients. (July 2022) - Giovannini, Silvia; Biscetti, Federico; Brau, Fabrizio; Biscotti, Lorenzo; Santoliquido, Angelo; Pitocco, Dario; Bernabei, Roberto; Flex, Andrea
Abstract: Background: The role of sortilin and omentin-1 in the pathogenesis of atherosclerosis and vascular disease is an emerging topic in recent years. These molecules can be found circulating in the blood. Recent studies have shown how these biomarkers appear to correlate with the severity of PAD. The levels of these molecules appear to be inversely proportional to each other. Their relationship may provide further insight into the management of the very old diabetic patients with PAD. This study aimed to assess the possible role of sortilin/omentin-1 ratio as easy-to-measure marker in peripheral artery disease (PAD) in type-2 diabetic patients. Methods: This study analyzed the association between sortilin and omentin-1 serum levels and the presence of clinically significant lower limb PAD in diabetic individuals. We enrolled 295 diabetic patients, including 179 with PAD. Serum levels were collected and correlated with clinical characteristics of the patients. Results: Sortilin concentration was significantly higher in the latter group compared to the former and there was a trend toward increased sortilin levels as disease severity increased. Omentin-1 serum levels were significantly lower in diabetic patients with PAD than in diabetic controls and the levels gradually decreased in proportion to disease severity. The ratio of sortilin to omentin-1 was significantly higher in patients with PAD compared to the other group. Conclusion: The sortilin to omentin-1 ratio appears to be a predictive factor for PAD in patients with type-2 diabetes and it may be a promising marker for clinically significant atherosclerosis of the lower limbs. Further studies are needed to confirm this finding and to evaluate its clinical usefulness. Highlights: Several studies reported an association among sortilin and omentin-1 with onset and progression of peripheral artery disease. Few studies have assessed circulating sortilin and omentin-1 in patients with PAD and no one on selected elderly population. Sortilin/omentin-1 represents a prognostic index for PAD in elderly related to lower limbs atherosclerosis.